Conversation Therapy with People with Aphasia and Conversation Partners using Video Feedback: A Group and Case Series Investigation of Changes in Interaction - Best, Wendy; Maxim, Jane; Heilemann, Claudia; Beckley, Firle; Johnson, Fiona; Edwards, Susan I.; Howard, David; Beeke, Suzanne (Frontiers in Human Neuroscience, 2016)
Conversation therapies employing video for feedback and to facilitate outcome measurement are increasingly used with people with post-stroke aphasia and their conversation partners; however the evidence base for change in everyday interaction remains limited. We investigated the effect of Better Conversations with Aphasia, an intervention that is freely available online (https:// extend.ucl.ac.uk/). Eight people with chronic agrammatic aphasia, and their regular conversation partners participated in the tailored 8 week program involving significant video feedback. We explored changes in (i) conversation facilitators (such as multi-modal turns by people with aphasia) and (ii) conversation barriers (such as use of test questions by conversation partners). The outcome of intervention was evaluated directly by measuring change in video-recorded everyday conversations. The study employed a pre-post design with multiple 5 minute samples of conversation before and after intervention, scored by trained raters blind to the point of data collection. Group level analysis showed no significant increase in conversation facilitators. There was, however, a significant reduction in the number of conversation barriers. The case series data revealed variability in conversation behaviors across occasions for the same dyad and between different dyads. Specifically, post-intervention there was a significant increase in facilitator behaviors for two dyads, a decrease for one and no significant change for five dyads. There was a significant decrease in barrier behaviors for five dyads and no significant change for three dyads. The reduction in barrier behaviors was considerable; on average change from over 8 to fewer than 3 barrier behaviors in 5 minutes conversation. The pre-post design has the limitation of no comparison group. However, change occurs in targeted conversational behaviors and in people with chronic aphasia and their partners. The findings suggest change can occur after eight therapy sessions and have implications for clinical practice. A reduction in barrier behaviors may be easier to obtain, although the controlled case series results demonstrate a significant increase in conversation facilitators is also possible. The rehabilitation tool is available online and video technology was central to delivering intervention and evaluating change.